The Mediterranean: high discovery rates for a well-studied trematode fauna - Pérez-del-Olmo, Ana; Kostadinova, Aneta; Gibson, David I (Systematic parasitology, 2016)
Our knowledge of trematode diversity in Mediterranean Sea fishes is based on many contributions since the early 1800s (e.g. by Rudolphi, Stossich, Looss, Bartoli, Bray and Gibson). We have updated data from the Natural History Museum Host-Parasite Database and listed 302 digenean trematode species allocated to 146 genera in 29 families from 192 fish species (27% of the known fish-fauna) belonging to 76 families. The most diverse (with 31-41 species) digenean families (Opecoelidae Ozaki, 1925, Didymozoidae Monticelli, 1888 and Hemiuridae Looss, 1899) represent more than a third of the total richness (36% of species) and have been most frequently recorded (43% of the records). The overall mean number of species per host is close to recent global estimates for digenean richness in teleosts (1.57 vs 2.04, respectively), indicating a high diversity in the Mediterranean. The most diverse host families are also the best studied. However, three speciose host families (Rajidae de Blainville, Gobiidae Cuvier and Myctophidae Gill) appear under-studied and no digenean reports exist for 94 of 169 fish families present in the Mediterranean. Thus, although Mediterranean fishes appear well studied, further efforts are needed. Nevertheless, the descriptions of a large number of new taxa since 2000 indicate that focused efforts have resulted in a high discovery rate (2.4 species per year). Many of these new (often cryptic) taxa are the result of combined morphological and molecular methods, which promise more reliable estimates of digenean diversity in this region. We provide host-parasite lists for 192 species of fish in the Mediterranean comprising 890 host-parasite associations.
Keywords: Biodiversity; Animals; výzkum; Classification; Fishes; Research; zvířata; ryby; Středozemní moře; Databases, Factual; klasifikace; Mediterranean Sea; biodiverzita; databáze faktografické; Trematoda